Evaluating Visual Table Data Understanding - Henry Riche, Nathalie; Fekete, Jean-Daniel (In Proceedings of the 2006 AVI workshop on BEyond time and errors: novel evaluation methods for information visualization, 2006)
In this paper, we focus on evaluating how information visualization supports exploration for visual table data. We present a controlled experiment designed to evaluate how the layout of table data affects the user understanding and his exploration process. This experiment raised interesting problems from the design phase to the data analysis. We present our task taxonomy, the experiment procedure and give clues about data collection and analysis. We conclude with lessons learnt from this experiment and discuss the format of future evaluation.